2013
DOI: 10.1242/jeb.087197
|View full text |Cite
|
Sign up to set email alerts
|

Ventilation patterns of the songbird lung/air sac system during different behaviors

Abstract: SUMMARYUnidirectional, continuous airflow through the avian lung is achieved through an elaborate air sac system with a sequential, posterior to anterior ventilation pattern. This classical model was established through various approaches spanning passively ventilated systems to mass spectrometry analysis of tracer gas flow into various air sacs during spontaneous breathing in restrained ducks. Information on flow patterns in other bird taxa is missing, and these techniques do not permit direct tests of whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…This cavity provides space for the ingluvies, trachea, and clavicular air sac (Yasuda, 2002). The clavicular air sac is one of the structures needed to phonate (Beckers et al 2003;Mackelprang and Goller, 2013). Beckers et al (2003) reported that the interclavicle air sacs serve as resonator that contribute to the production of pure tones in songbirds.…”
Section: Characteristics Related To Attractiveness Of An Ornamental Fowlmentioning
confidence: 99%
See 1 more Smart Citation
“…This cavity provides space for the ingluvies, trachea, and clavicular air sac (Yasuda, 2002). The clavicular air sac is one of the structures needed to phonate (Beckers et al 2003;Mackelprang and Goller, 2013). Beckers et al (2003) reported that the interclavicle air sacs serve as resonator that contribute to the production of pure tones in songbirds.…”
Section: Characteristics Related To Attractiveness Of An Ornamental Fowlmentioning
confidence: 99%
“…Beckers et al (2003) reported that the interclavicle air sacs serve as resonator that contribute to the production of pure tones in songbirds. Mackelprang and Goller (2013) report that vibrations of the labia and membranes, which affect gating of airflow and acoustic parameters such as frequency, are generated by the pressure of interclavicle air sacs. Jones and Witt (2014) reported that the length of trachea, which generates the sound in crowing, is limited by the sternum in cranes.…”
Section: Characteristics Related To Attractiveness Of An Ornamental Fowlmentioning
confidence: 99%
“…Nevertheless, pressure differences between anterior and posterior sacs are possible during vocalization. During cooing in doves, for instance, a significant pressure difference has been recorded between the clavicular and caudal thoracic sacs, which could imply a measure of independent control of pressure in different air sacs, with possible implications for vocalization (Beckers et al, 2003; see also Mackleprang and Goller, 2013). …”
Section: Peripheral Mechanics Of Breathing In (Song)birdsmentioning
confidence: 99%
“…Due to the formation of this once‐through approach allowing for a continued flow through the lung with fresh and depleted air reservoirs, the overall one‐pass oxygen separation efficiency is dramatically improved over the mammalian system, where for resting humans 28% of inhaled air does not reach the respiratory surfaces at all . Further, because this system does not rely on exchange through alveoli which must expand and contract while maintaining a certain compliance when fully exhaled that they do not fully collapse, this topological configuration allows for smaller hydrodynamic diameters within the exchange section, thus improving the overall volumetric efficiency of the lungs by orders of magnitude …”
Section: Adopting a New Reactor Design Methodology To Harness Modern mentioning
confidence: 99%
“… Schematic of avian lung, reprinted with permission from. The avian lung is topologically distinct from the mammalian lung, with two air sacs (e) and (b) and two valves (V1) and (V2) which work in concert to supply a steady unidirectional flow through the primary exchange surface (d). …”
Section: Adopting a New Reactor Design Methodology To Harness Modern mentioning
confidence: 99%